Influence of Information Technology Investment on Indonesian Bank Profitability with Size Moderation - Quinasa Rama Herlanlam; Osly Usman (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This research aims to explore the influence of information technology investment on bank profitability in Indonesia, with firm size as a moderating variable. This research is an associative research with quantitative approach. The methodology employed is panel data regression analysis, utilizing a purposive sampling technique, and a sample of 24 banks listed on the Indonesian Stock Exchange from 2019 to 2023. The analyzed data includes information on information technology investments, profitability measured by return on assets and return on equity, and firm size represented by total assets. The findings reveal that information technology investment positively and significantly affects bank profitability in terms of both return on assets and return on equity. However, the hypothesis stating that firm size strengthens the influence of information technology investment on return on assets was rejected, indicating that there is a time lag in realizing the full benefits of technology investments on asset efficiency. Conversely, the hypothesis that firm size strengthens the impact of information technology investment on return on equity was accepted, suggesting that larger banks can leverage technology investments more effectively to enhance their profitability. These findings hold important applications for bank managers in planning technology investment strategies, particularly in the context of improving operational efficiency and competitiveness in an increasingly digital banking industry. This study also contributes to the literature on information technology investment and financial performance in the banking sector.